Significant nonlinear‐optical switching capacity in atomic clusters built from silicon and lithium: A combined ab initio and density functional study. Issue 11 (12th February 2014) - Karamanis, Panaghiotis; Otero, Nicolás; Pouchan, Claude; Torres, Juan José; Tiznado, William; Avramopoulos, Aggelos; Papadopoulos, Manthos G.
<x xml:space="preserve">Abstract</x> Starting from a hypothetical but fundamental charge/discharge sequence, the topic of nonlinear optical switching in atomic clusters built from silicon and alkali metals is opened up. The outcomes presented in this work, obtained with ab initio methods of exceptional predictive capabilities, offer strong evidences that sizable hyperpolarizability contrasts between neutral and charged alkali metal doped cluster forms might be simultaneously accomplished. The observed switching procedure involves redox polyatomic clusters formed by Si atoms. These centers function as electron acceptors at the ground state and as electron donors at the excited states facilitating low energy charge transfer transitions upon electronic excitation. © 2014 Wiley Periodicals, Inc.